Comparison of the effects of continuous positive airway pressure, oral appliance and exercise training in obstructive sleep apnea syndrome (Clinics, 2013)
OBJECTIVE: There are several treatments for obstructive sleep apnea syndrome, such as weight loss, use of an oral appliance and continuous positive airway pressure, that can be used to reduce the signs and symptoms of obstructive sleep apnea syndrome. Few studies have evaluated the effectiveness of a physical training program compared with other treatments. The aim of this study was to assess the effects of physical exercise on subjective and objective sleep parameters, quality of life and mood in obstructive sleep apnea patients and to compare these effects with the effects of continuous positive airway pressure and oral appliance treatments. METHODS: Male patients with moderate to severe obstructive sleep apnea and body mass indices less than 30 kg/m2 were randomly assigned to three groups: continuous positive airway pressure (n = 9), oral appliance (n = 9) and physical exercise (n = 7). Polysomnographic recordings, blood samples and daytime sleepiness measurements were obtained prior to and after two months of physical exercise or treatment with continuous positive airway pressure or an oral appliance. Clinicaltrials.gov: NCT01289392 RESULTS: After treatment with continuous positive airway pressure or an oral appliance, the patients presented with a significant reduction in the apnea-hypopnea index. We did not observe changes in the sleep parameters studied in the physical exercise group. However, this group presented reductions in the following parameters: T leukocytes, very-low-density lipoprotein and triglycerides. Two months of exercise training also had a positive impact on subjective daytime sleepiness. CONCLUSIONS: Our results suggest that isolated physical exercise training was able to modify only subjective daytime sleepiness and some blood measures. Continuous positive airway pressure and oral appliances modified the apnea-hypopnea index.